Smart-blacklisting:an efficient methodology for mitigating fake block attack in P2P file-sharing systems - Ru-hao YAO; Bing-shuang LIU; De-shuai QU; Yuan ZHOU; Xin-hui HAN (Tongxin xuebao)
Fake block attack intends to prolong the downloading time by providing fake data to make the file block fail in the hash check.P2P file-sharing systems are susceptible to fake block attacks,whereby malicious clients are able to make a big impact on users’ downloading experience.An efficient methodology named Smart-blacklisting,which aims to lessen the downloading time and bandwidth wastes interfered by the attack was proposed through using a mathematic model,and the efficiency of this method was analyzed during a simulation experiment.The ovel approach presents 87% downloading time and 50% bandwidth wastes compare less than those of eMule blacklisting method.